Effect of Novel Remodeled Bicycle Pedal Training on Balance Performance in Athletes With Functional Ankle Instability - Yi-Shuo Chang (Frontiers in Bioengineering and Biotechnology, 2020)
ContextAppropriate training without risk of injury is a critical concern for athletes. Remodeled bicycle pedal training with multi-directional challenges may be effective in improving the balance performance of athletes with functional ankle instability (FAI).ObjectiveTo evaluate the effects of 6-week modified bicycle pedal training on the balance ability and proprioception of athletes with FAI.DesignRandomized controlled trial.SettingUniversity motion analysis laboratory.ParticipantsFourteen healthy athletes (healthy group) and twenty-six athletes with FAI and an age of 18 to 30 years old. The participants with FAI were randomly distributed to two groups, designated as the training group (AI-T group) and non-training group (AI-NT group), respectively. The athletes in the AI-T group received 6-week remodeled bicycle pedal training, while those in the AI-NT group received no intervention at all.InterventionA 6-week training using modified bicycle pedal capable of moving freely during loading cycle vs no intervention.Main Outcome MeasuresThe passive ankle joint position sense (JPS) in four angles and the center of pressure (COP) parameters were analyzed during single-leg standing with and without vision, respectively.ResultsA 6-week remodeled pedal training: (1) significantly improved the passive JPS of ankle in all directions (P < 0.05); (2) reduced the excursion of the COP in the medial-lateral (ML) direction (p < 0.05), the velocity of the COP in the ML direction (p < 0.05), and the RMS of the COP in the ML direction (P < 0.05) during single-leg standing both with and without vision.ConclusionThe remodeled bicycle pedal training improved the passive JPS and reduced the postural sway in single-leg standing both with and without vision. Therefore, remodeled bicycle pedal training can be considered for inclusion in rehabilitation programs for athletes with FAI to restore the proprioception and balance ability.